High-impact educational practices in higher education institutions: a thematic review / Noor Syahida Md Soh... [et al.] - Md Soh, Noor Syahida; Mohd Sairi, Faridah; Ayob, Mohd Annas Shafiq; Mohamad, Mafuzah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
High Impact Educational Practices (HIEPs) have been identified as effective in providing positive educational results for students from diverse backgrounds across several institutions. Despite its effectiveness in teaching and learning, prior research revealed that there is still a lack of review papers discussing the trend in the application of High Impact Educational Practices (HIEPs), specifically in Higher Education Institutions. Therefore, this thematic review (TR) paper aims to discuss the most common High Impact Educational Practices (HIEPs) applied in teaching at the university by synthesizing the literature from 2019 to 2023 using ATLAS.ti 23. A keyword search, followed by a filter using inclusion criteria from SCOPUS, WoS, and Science Direct databases, identified 39 peer-reviewed journal articles. However, after the inclusion and exclusion processes, only 24 articles were considered to be used as the final articles to be reviewed. A thematic review of 24 articles identified 27 initial codes grouped into the five most practiced HIEPs in Higher Education Institutions worldwide. The five main themes are collaborative, service, experiential, research-based, and engaged learning. The results of this study will benefit future studies on the application of HIEPs in teaching at the university level. They can be the main guideline for developing a sustainable practice framework for applying HIEPs.